Going dark the contemporary figure at the edge of visibility - James, Ashley ca. 20./21.Jh; Carter, Jordan; Cortez, Rio; Dozier, Ayanna; Helal, Marwa ca. 20. Jh; Henson, Kristian; Holiday, Harmony; Lee, Key Jo; Mutiti, Nontsikelelo; Rahim, Hassan; Russell, Legacy 1986-; Scriber, Abbe; et al. (Guggenheim, 2023)
"Going Dark brings together a multigenerational group of contemporary artists who engage the "semi-visible" figure-representations that are partially (or fully) obscured, including, in some cases, literally darkened-and suggests that the concept of going dark is a tool that has been used by artists for decades to probe enduring questions surrounding both the potential and the discontents of social visibility. Across mediums-painting, photography, sculpture, video and installation-Going Dark names, charts and makes meaning of the semi-visible figure, arguing for its significance in contemporary art as a genre of unique conceptual and formal power. More than 125 works in all of these mediums by more than 25 artists are featured. Essays by such curators as Legacy Russell and Jordan Carter, and professor Abbe Schriber, among others, contextualize the histories that inspired these works. In addition, four award-winning poets and three acclaimed graphic designers have contributed works. Artists include: American Artist, Kevin Beasley, Rebecca Belmore, Dawoud Bey, John Edmonds, Ellen Gallagher, David Hammons, Lyle Ashton Harris, Tomashi Jackson, Titus Kaphar, Glenn Ligon, Kerry James Marshall, Tiona Nekkia McClodden, Joiri Minaya, Sandra Mujinga, Chris Ofili, Sondra Perry, Farah Al Qasimi, Faith Ringgold, Doris Salcedo, Lorna Simpson, Sable Elyse Smith, Stephanie Syjuco, Hank Willis Thomas, WangShui, Carrie Mae Weems and Charles White."
Impressum: 'Published on the occasion of the exhibition 'Going Dark: The Contemporary Figure at the Edge of Visibility', Solomon R. Guggenheim Museum, New York, October 20, 2023 - April 7, 2024'
Keywords: Geschichte 2000-2023; Human beings in art / Exhibitions; Shades and shadows in art / Exhibitions; Absence in art / Exhibitions; Art, Modern / 21st century / Exhibitions; Absence in art; Art, Modern; Human beings in art; Shades and shadows in art; Unsichtbarkeit; Dunkelheit -- Motiv; Kunst; Ausstellungskatalog -- Solomon R. Guggenheim Museum -- 20.10.2023-07.04.2024 -- New York, NY; Aufsatzsammlung